2021
DOI: 10.3390/microorganisms9071459
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Pig Fecal Microbiota Composition and Diversity in Response to Enterotoxigenic Escherichia coli Infection and Colistin Treatment in Weaned Piglets

Abstract: The intestinal microbiota plays several important roles in pig health and growth. The aim of the current study was to characterize the changes in the fecal microbiota diversity and composition of weaned piglets following an oral challenge with an ETEC: F4 strain and/or a treatment with colistin sulfate (CS). Twenty-eight piglets were used in this experiment and were divided into four groups: challenged untreated, challenged treated, unchallenged treated, and unchallenged untreated. Rectal swab samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
3
14
0
Order By: Relevance
“…Gut microbiota is known as a regulator of intestinal health and growth performance of pigs ( Qi et al, 2021 ). Similar to a previous study ( Rhouma et al, 2021 ), this study showed that the ETEC challenge caused gut microbiota dysbiosis of piglets, as evidenced by obvious changes in β-diversity and bacterial proportions of gut microbiota, however, these changes were largely reversed by GOD addition. Among the bacteria changed by GOD addition, Fusobacterium spp.…”
Section: Discussionsupporting
confidence: 88%
“…Gut microbiota is known as a regulator of intestinal health and growth performance of pigs ( Qi et al, 2021 ). Similar to a previous study ( Rhouma et al, 2021 ), this study showed that the ETEC challenge caused gut microbiota dysbiosis of piglets, as evidenced by obvious changes in β-diversity and bacterial proportions of gut microbiota, however, these changes were largely reversed by GOD addition. Among the bacteria changed by GOD addition, Fusobacterium spp.…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with the positive effect of C_ZnO on gut flora, the increased concentration of acetate and propionate also confirmed a more harmonious intestinal environment. Streptococcus had been found to be correlated with piglet body weight and commonly related to the healthy structure of microbiota (39,40) in accordance with the improved growth performance in the group. Interestingly, our results also found Streptococcus was gathered in the colonic lumen in the CON group to some extent, rather than ileal lumen.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, Lachnospiraceae and Lactobacillaceae have been proposed and investigated as biomarkers to predict the health status of pigs [ 57 , 58 ]. Rhouma et al [ 59 ] demonstrated that the ETEC F4 challenge suppressed the relative abundance of Lachnospiraceae and Lactobacillaceae in fecal contents of pigs, compared with unchallenged pigs. In addition, Dou et al [ 60 ] also reported that diarrheic pigs, in natural post-weaning diarrhea, had a lower abundance of Lachnospiraceae and Lactobacillaceae in feces, compared with healthy pigs.…”
Section: Discussionmentioning
confidence: 99%